Clinical Outcomes From The Bioresorbable Vascular Scaffold: Is There A Role for Them? - Rashid, Shabnam (Cardiology and Cardiovascular Medicine, 2016)
The risk of stent thrombosis and restenosis with the second generation drug eluting stents remains. The bioresorbable vascular scaffold is a third generation stent and overcomes the problems associated with drug eluting metallic stents. The bioresorbable vascular scaffold completely absorbs within the coronary vessel over 3-5 years. Multiple trials in patients with non complex coronary disease have demonstrated similar outcomes with regards to cardiac death, myocardial infarction and target vessel revascularisation when comparing the bioresorbable vascular scaffold with the second generation everolimus eluting metallic stents. However, the occurrence of device related thrombosis appears to be higher with the scaffold.